Probability of error calculation of OFDM systems with frequency offset. - Sathananthan, K.
Orthogonal frequency-division multiplexing (OFDM) is sensitive to the carrier frequency offset (CFO), which destroys orthogonality and causes intercarrier interference (ICI), Previously, two methods were available for the analysis of the resultant degradation in performance. Firstly, the statistical average of the ICI could be used as a performance measure. Secondly, the bit error rate (BER) caused by CFO could be approximated by assuming the ICI to be Gaussian. However, a more precise analysis of the performance (i.e., BER or SER) degradation is desirable. In this letter, we propose a precise numerical technique for calculating the effect of the CFO on the BER or symbol error in an OFDM system. The subcarriers can be modulated with binary phase shift keying (BPSK), quaternary phase shift keying (QPSK), or 16-ary quadrature amplitude modulation (16-QAM), used in many OFDM applications. The BPSK case is solved using a series due to Beaulieu (1990). For the QPSK and 16-QAM cases, we use an infinite series expression for the error function in order to express the average probability of error in terms of the two-dimensional characteristic function of the ICI
Keywords: 16-QAM.; BER; BPSK; OFDM systems; QPSK; Average error probability; Binary phase shift keying; Bit error rate; Carrier frequency offset; Infinite series expression; Intercarrier interference; Orthogonal frequency-division multiplexing; Precise numerical technique; Quadrature amplitude modulation; Quaternary phase shift keying; Symbol error rate